Pendekatan Multikulturalisme dalam Menumbuhkan Budaya Toleransi di SMA Negeri 6 Kupang - Marquita Seuk Seran (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2025)
This study aims to (a) analyze the implementation of a multicultural approach in fostering a culture of tolerance at SMA Negeri 6 Kupang, and (b) identify the values of tolerance developed in the school community. This research used a descriptive qualitative method, with participants consisting of the Vice Principal for Student Affairs, a Sociology teacher, and tenth-grade students. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data presentation, and conclusion drawing techniques. The findings reveal that six multicultural approaches are implemented in the school environment, including appreciation for diversity, equality, tolerance, intercultural dialogue, social inclusion, and recognition of cultural identity. These approaches are reflected in learning activities, student interactions, and school programs that promote intercultural communication. Values developed through these approaches include social values, diversity, respect for others' opinions, and interreligious harmony. The implementation has contributed to an inclusive and harmonious school atmosphere, promoting empathy and mutual respect. However, several challenges remain, such as stereotypes, discriminatory behavior, and students’ uneven awareness of diversity. Therefore, continuous collaboration among school stakeholders, families, and the community is required to strengthen sustainable tolerance values.